Interconnection of Islamic Economics and Pancasila in the Economic Management System in Indonesia (Analysis of Thought Theory of KH. Achmad Siddiq Jember) - Maulana, Muhammad Elton Rasyid (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Viewed from a normative perspective, religious teachings influence the economic activities of the previously implemented economic system. On the other hand, the Islamic economic system earlier inspired the formation of the economic system that is currently implemented in Indonesia, namely the Pancasila economic system. In essence, Indonesia is a unique country and can be a role model for an economic system that comes from the synchronization of Islamic economics and Pancasila. To review this further, this study aims to analyze the meeting point of the relationship between the two economic systems in the context of economic management as taught through Surah Yusuf verses 47-49, Al-Ashr verses 1-3, and HR. Al-Baihaqi. In addition, the author analyzes the theory of KH Achmad Siddiq's thinking as the main theoretical basis for this purchase. In the process, this study uses qualitative descriptive method analysis through literature studies from several journals, books, or supporting data. The results of the study show that there are several similarities and differences between Islamic and Pancasila economic management. Where both are intended to equalize social justice for both oneself and the wider community. This has been synchronized with the interpretation of verses and hadith, stages of economic management, basic principles of Islamic economics, and the economic value content of Pancasila.